Pengembangan Media Visual Maket Materi Mengidentifikasi Lambang/Simbol untuk Siswa Kelas III SDN Mojoroto 4 Kota Kediri - Juwariyatuz Zekiyah; Endang Sri Mujiwati; Rian Damariswara (STKIP PGRI SITUBONDO, 2022)
This research was motivated by the result of observations at SDN Mojoroto 4 Kediri City in grade 3 student. It was found that students understanding of the material symbols/ symbols (traffic signs, scouts, and state symbols) was not maximized. This happens because teachers have not found learning media that can help students learning process in understanding the material symbols/ symbols (traffic signs, scouts, and state symbols). This study aims to determine the validity of the media, the teachers response, and the effectiveness of the maket visual media. in this study using the Borg and Gall development model. Furthermore, the techniques used in collecting data in the form of a questionnaire include a media construction validation questionnaire, a material validation questionnaire, a teacher response questionnaire to maket visual media, and a written test. The result of the research on the development of the maket visual media are as follows: (1) the maket visual media is declared valid and can be used without revision with a percentage of 95%, (2) material symbols/ symbols (traffic signs, scouts, and state symbols) declared valid and can be usedin the learning process with a percentage 92,5%, (3) the teacher response to the media is declared good and can be used in the learning process by the percentage is 100%, and (4) maket visual media is declared effective and can be used in the learning process with a classical completeness percentage of 75%. Based on the result of the research above, it can be concluded tha the maket visual media is valid and suitable for use in learning Indonesian language subjects with symbols/ symbols (traffic signs, scouts, and state symbols).